Case Report: Relapsed Pulmonary Tuberculosis With Drug-Induced Hepatotoxicity And Severe Malnutrition - Syazili Mustofa; Salva Amanda Shafira; Giska Tri Putri; Hendri Busman; Denara Eka Safitri (Jurnal Ilmu Kedokteran dan Kesehatan, 2026)
Relapsed pulmonary tuberculosis (TB) remains a major clinical challenge, particularly when complicated by drug-induced liver injury (DILI) and severe malnutrition. We report the case of a 54-year-old man with a history of bacteriologically confirmed pulmonary TB who presented with progressive dyspnea, productive cough, fever, night sweats, decreased appetite, and weight loss. After restarting anti-tuberculosis therapy, he developed jaundice, nausea, and vomiting. Physical examination revealed bilateral rhonchi, conjunctival pallor, scleral icterus, and severe underweight status. Laboratory evaluation showed microcytic hypochromic anemia, leukocytosis, hyponatremia, hypokalemia, hypocalcemia, severe hypoalbuminemia, hyperbilirubinemia, and markedly elevated transaminases. He was diagnosed with relapsed pulmonary TB complicated by DILI, community-acquired pneumonia, anemia of chronic disease, electrolyte imbalance, and severe malnutrition. Management included discontinuation of anti-tuberculosis drugs, supportive care, antibiotics, electrolyte correction, albumin supplementation, nutritional therapy, and gradual reintroduction of anti-tuberculosis treatment after clinical and biochemical improvement. After undergoing inpatient care for 2 weeks, the patient showed progressive clinical improvement with declining liver enzyme levels, allowing successful stepwise reintroduction of anti-tuberculosis therapy, and was discharged with a plan for continued outpatient follow-up. This case highlights the importance of early recognition of hepatotoxicity, comprehensive supportive management, and individualized stepwise reintroduction of anti-tuberculosis therapy in complex TB cases.